FACTORS AFFECTING THE ACADEMIC PERFORMANCE OF ACCOUNTING UNDERGRADUATES IN SRI LANKAN STATE UNIVERSITIES - M.A. Gayantha N. Jayasooriya; Roshan Ajward (ZILLZELL MEDIA PRIMA, 2025)
This study investigated factors affecting the academic performance of accounting undergraduates in Sri Lanka's state universities. Seventeen factors related to the university system, demographics, and personal characteristics were analyzed using a quantitative approach with 287 valid responses collected via a self-administered questionnaire. Descriptive statistics and inferential analyses, including one-way ANOVA, t-tests, correlation, and OLS regression, were used to assess the impact of these factors on academic performance. The average GPA of students was between 3.30 and 3.69 (second-class upper division). Key factors positively associated with academic performance included being female, fewer distractions from seniors, commuting from boarding places, higher engagement in extracurricular activities, prior English and mathematics knowledge, and taking professional accounting courses. Other factors showed no significant impact. The study offers insights for academicians, policymakers, and students to improve academic performance through structural adjustments and effective strategies.